2013
DOI: 10.1155/2013/129841
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Lifestyle Medicine: Relevance for Nutrition and Lifestyle Recommendations

Abstract: Public health recommendations for lifestyle modification, including diet and physical activity, have been widely disseminated for the prevention and treatment of disease. These guidelines are intended for the overall population without significant consideration for the individual with respect to one's genes and environment. Personalized lifestyle medicine is a newly developed term that refers to an approach to medicine in which an individual's health metrics from point-of-care diagnostics are used to develop l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 81 publications
2
51
0
Order By: Relevance
“…Population-based health recommendations have limited efficacy in promoting health behavioral changes [1,2,3]. This may be due to individual differences in responding to dietary changes because of nutrient-gene interactions [2].…”
Section: Introductionmentioning
confidence: 99%
“…Population-based health recommendations have limited efficacy in promoting health behavioral changes [1,2,3]. This may be due to individual differences in responding to dietary changes because of nutrient-gene interactions [2].…”
Section: Introductionmentioning
confidence: 99%
“…The principal objective of PM about nutrition is to render the efficacious approach to manage diseases with totally dependent on "the genetics, lifestyle (dietary, exercise and lifestyle choices), metabolic status, gut microbiota and physiological status (nutrient level and disease status)" of any patient without any bad outcome 126 . It has been reported that multiple chronic hereditary metabolic clinical problems can be adequately managed in precision nutritional care [127][128][129] . Three most significant areas need to measure in precision nutrition that comprises discrete principles for adequate nutritional "status, biomarker monitoring or techniques for nutrient detection and the applicable therapeutic or intervention methods" 126 .…”
Section: Nutritional Diseases and Precision Medicinementioning
confidence: 99%
“…Furthermore, a polymorphism within the MPO gene (rs2333227) is associated with hypertension [60] and cancer risk, with the latter genetic relationship being mitigated through diet [61]. Conversely the association between plasma levels of MPO and hypertension is strengthened in the presence of hyperglycemiainduced oxidative stress, which could be targeted in a personalized nutritional program [62,63].…”
Section: Metabolomics the Gut Microbiome And Nutrigeneticsmentioning
confidence: 99%